Field day on the need of organisational farmers entity to have easy access to NT seeder - Moussadek, Rachid (2023)
The lists of beneficiaries of the various partners must be drawn up according to the predefined outlines which was transmitted by the DDFA/DRA RSK to the representatives of the partners then shared with the coordinators of the partners according to the decisions taken during the last meeting of the Steering Committee and this before 21/11/2022; - Ensure compliance with eligibility criteria when choosing takeover bids/beneficiaries. These criteria must be unified at the level of all the partners; - Identify young agricultural entrepreneurs from a service company/cooperative agriculture (direct seeding) to benefit from the equipment acquired or in progress acquisition;